Evaluasi Kesesuaian Tugas, Beban Kerja, Penjadwalan Waktu Kerja, dan Regulasi Pemerintah Terhadap Kinerja Relawan SPPG (Studi Kasus Pada SPPG di Pugung Raharjo, Lampung Timur): (Studi Kasus Pada SPPG di Pugung Raharjo, Lampung Timur) - Sartika Agustin; Fitriyani Fitriyani; Trisnowati Josiah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
The Satuan Pelayanan Pemenuhan Gizi (SPPG) program represents a volunteer-based public service initiative that plays an important role in supporting community nutritional fulfillment. The success of this program largely depends on the performance of volunteers as operational implementers in the field. However, volunteer management still faces several challenges, including disproportionate task distribution, high workload, less structured work scheduling, and the dynamics of government regulations. This study aims to evaluate the influence of task suitability, workload, work scheduling, and government regulations on the performance of SPPG volunteers in Pugung Raharjo, East Lampung. This research employs a mixed methods approach with a sequential explanatory design, in which quantitative analysis is followed by qualitative exploration to deepen the interpretation of the findings. The research population consisted of all active SPPG volunteers totaling 49 individuals, selected using a total sampling technique. Data were collected through questionnaires and field observations and analyzed using partial tests (t-test), simultaneous tests (F-test), and thematic analysis for qualitative data. The results indicate that task suitability and workload have a positive and significant effect on volunteer performance, while work scheduling and government regulations do not have a significant partial effect. However, simultaneously, the four variables significantly influence volunteer performance, with a coefficient of determination of 85.6%. These findings suggest that effective volunteer management, particularly in task allocation and workload management, plays a crucial role in improving the performance of SPPG volunteers. This study recommends improving volunteer management systems, especially in work ratio arrangements, shift systems, and operational support to enhance the sustainability of community nutrition services.